2008
DOI: 10.1080/14786430802342576
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation of creasing in corrugated paperboard

Abstract: International audienceCreasing is a process which indents a section of corrugated board along fold lines to facilitate a neat fold. Most common failure site in a box made out of corrugated board is at the folds, where the stiffness is reduced by the creasing operation. Crease depth is an important parameter to be controlled. If the crease is too shallow, the section will crack during folding due to excessive strain on the outer liner. On the other hand, if the crease is too deep, the board may crack during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…Moreover, Isaksson and Hägglund (2005) use the crack tip energy release rate as a failure criterion for delamination. Beldie (2001), Barbier et al (2004) and Thakkar et al (2008) used conventional Hill-plasticity to simulate the responses of both paperboard and corrugated board.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Isaksson and Hägglund (2005) use the crack tip energy release rate as a failure criterion for delamination. Beldie (2001), Barbier et al (2004) and Thakkar et al (2008) used conventional Hill-plasticity to simulate the responses of both paperboard and corrugated board.…”
Section: Introductionmentioning
confidence: 99%
“…the folding lines are scored onto the paperboard by pressing it by a male die with a rule onto a grooved female die. The creasing locally damages the paperboard reducing its bending stiffness and promoting the folding around the design lines [14,22,32,6].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the creasing process of a fluted material, Harryson et al (4) and Thakkar et al (5) reported about the anisotropic model analysis of Cfb, which was subjected to a creaser indentation, but there was not any discussion about the failure mechanism on the liner. There is not any study of the failure behaviors of the Cm, the outside liner and the inside liner sheet when the failure occurred using a rotary creaser, owing to its complicated structure and to difficulties of taking measurement while performing the process.…”
Section: Introductionmentioning
confidence: 99%